Determinants of Lecturer Performance: Systematic Literature Review (SLR) Approach - Sukarelawan, Asep Ganjar; Hamid, Eka Abdul; Qomusuddin, Ivan Fanani; Wemama, A-eshah (JURNAL AL-TANZIM, 2025)
This study aims to identify and map the key determinants of lecturer performance using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. A total of 30 Scopus-indexed scientific articles (Q1–Q4), published between 2015 and 2025, were systematically analyzed. The findings reveal seven dominant factors affecting lecturer performance: organizational commitment, job satisfaction, work motivation, lecturer competence, organizational culture, organizational citizenship behavior (OCB), and transformational Leadership. Among these, individual factors emerged as the most prevalent, followed by organizational culture and Leadership. These results indicate that lecturer performance is a multidimensional construct shaped by psychological, structural, and contextual dimensions. The study contributes theoretically by integrating diverse perspectives into a holistic conceptual framework and provides practical insights for developing human resource policies in higher education, particularly within private religious institutions. However, as a secondary literature analysis, the validity of these findings requires further empirical investigation within localized contexts, including the role of variables such as lecturer certification and Islamic Leadership.